2004
DOI: 10.1577/02-103
|View full text |Cite
|
Sign up to set email alerts
|

Relationship among Fish Assemblages and Main‐Channel‐Border Physical Habitats in the Unimpounded Upper Mississippi River

Abstract: Large rivers worldwide have been altered by the construction and maintenance of navigation channels, which include extensive bank revetments, wing dikes, and levees. Using 7 years of Long‐Term Resource Monitoring Program (LTRMP) data collected from the unimpounded upper Mississippi River, we investigated assemblages in two main‐channel‐border physical habitats—those with wing dikes and those without wing dikes. Fishes were captured using daytime electrofishing, mini‐fyke netting, large hoop netting, and small … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 42 publications
3
43
0
Order By: Relevance
“…The assemblage of species that make up fish communities within a river/stream network is attributed mostly to how individual species distributions respond to patterns in vegetated patches (Araujo-Lima et al, 1986;Growns et al, 2003;Pelicice et al, 2008), hydrological connectivity (Amoros & Bornette, 2002;Petry et al, 2003), water transparency (Rodríguez & Lewis, 1997;Reyjol et al, 2008;Melo et al, 2009), physicochemical variables (Koné et al, 2003;Barko et al, 2004), food resources availability (Grenouillet & Pont, 2001), and prey-predator interactions (Piana et al, 2006) among others.…”
Section: Introductionmentioning
confidence: 99%
“…The assemblage of species that make up fish communities within a river/stream network is attributed mostly to how individual species distributions respond to patterns in vegetated patches (Araujo-Lima et al, 1986;Growns et al, 2003;Pelicice et al, 2008), hydrological connectivity (Amoros & Bornette, 2002;Petry et al, 2003), water transparency (Rodríguez & Lewis, 1997;Reyjol et al, 2008;Melo et al, 2009), physicochemical variables (Koné et al, 2003;Barko et al, 2004), food resources availability (Grenouillet & Pont, 2001), and prey-predator interactions (Piana et al, 2006) among others.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, fish community metrics did not suggest significantly "improved" or "healthier" fish communities in streams with wetland-dominated watersheds, as might be expected. Although fish community metrics tended to be greater in most wetland streams (e.g., Gregory et al, 1991;Heatherly and Whiles, 2007), metric values were highly variable both spatially and temporally; thus, between-stream type differences were not detecTable Several studies (e.g., Karr et al, 1985;Lisle and Hilton, 1992;Barko et al, 2004) have associated improved or otherwise healthier fish communities with factors such as low sediment deposition and low degrees of channel alteration, which are factors more associated with wetland streams in this study. In addition, other studies (e.g., Walser and Bart, 1999;Heitke et al, 2006) have observed greater fish species diversity and richness in streams with forested watersheds compared to streams with agricultural watersheds.…”
Section: Discussionmentioning
confidence: 53%
“…Fish assemblages were compared between both gears with the groupings either being completely separated (R > 0.75), overlapping but noticeably different (R -0.5), or barely separable (R < 0.25) (Clarke andWanvick 2001, Utrup andFisher 2006). Because sample size varied between gears, we used rarefaction to compare species richness between OTOl and OT16 (Simberloff 1972, Barko et al 2004, software by Holland 2003. Samples were standardized to correct for differences in effort allocation between trawl types.…”
Section: Discussionmentioning
confidence: 99%
“…Samples were standardized to correct for differences in effort allocation between trawl types. We randomized samples (without replacement) and resampled to the smallest sample size (OT01; N = 661) (Barko et al 2004). Rarefaction is a statistical tool used to calculate expected number of species at a site when a given number of fish are collected (Sanders 1968, Hurlbet 1971, Simberloff 1972).…”
Section: Discussionmentioning
confidence: 99%